Determinantes das emissões de gases de efeito estufa da economia brasileira: uma análise de decomposição estrutural (2010 a 2017) - Campos, Carlos Eduardo Espinel (Universidade Federal de São Carlos, 2021)
The evolution of the concentration of different gases in the Earth's atmosphere is a worrying phenomenon, because the ongoing process of global warming is not explained only by natural causes and is largely due to greenhouse gas emissions (GHGs), which are aggravated by human activities, in particular transport-related emissions. Thus, this study aims to assess the structural changes in the Brazilian economy (level of intensity, technology, structure of final demand, volume of final demand, size of the population, among others) related to GHG emissions, from both an aggregate and sectoral point of view and, in this case, focusing on the transport sector, which is responsible for a large volume of GHGs emitted in Brazil. The methodology applied was the structural decomposition analysis (SDA) with an environmental approach, based on input-output matrices estimated for Brazil, between 2010 and 2017 and data from the Sistema de Estimativa de Emissões e Remoções de Gases de Efeito Estufa (SEEG). The results showed that Brazil showed an increase in its level of GHG emissions, fueled both by technological effects and by effects linked to final demand. Therefore, the intensity of emissions and changes in production technologies in economic sectors, combined with population growth and the level of final demand, have contributed to the increase in pollutant emissions in the country. From a sector perspective, the ‘Land Transport’ sector has been characterized as an intense pollutant, as it emits a high level of pollution per monetary unit produced and indirectly influences GHG emissions in other economic activities.
Determinants of greenhouse gas emissions in the Brazilian economy: a structural decomposition analysis of (2010-2017)
Keywords: Insumo-Produto; Mudanças Estruturais; Emissões; Input-Output; Structural Changes; Emissions; CIENCIAS SOCIAIS APLICADAS::ECONOMIA